PENGARUH TINGGI MUKA AIR TANAH TERHADAP BEBERAPA SIFAT FISIK DAN KIMIA TANAH GAMBUT DI DESA KUALA DUA KABUPATEN KUBU RAYA - Simatupang, Darbin; Astiani, Dwi; Widyastuti, Tri (JURNAL HUTAN LESTARI, 2018)
Peatland is the result of organic matter accumulation from the decaying vegetation with naturally occuring through long term decomposition processes. The purpose of this study was to gain the information about the effect of water table level on some peatland chemical and physical properties of Kuala Dua village, Kubu Raya regency. The method used in this study was experiment al study the soil samples on 3 (three) water table levels were while examinated. Experimental study with completely randomized design using soil sampels of three water table levels 30 cm, 50 cm, and 80 cm with three replication. The result of this study showed that the depth 0-40 cm of water table level had the range values of soil water contents (397,3-460,5%), soil bulk density (0,18-0,25g/cm3), cation exchange capacity (116,4-118,4 mEq), soil organic carbon (56,8-57,5%), nitrogen (1,89-1,91%), soil phosporus (38,84-267,17%), soil humidity (8,2-9,9 %RH), soil potential hydrogen (3,04-3,17) and soil temperature (27,3-29,3ËšC). Base on the results, soil temperature and soil humidity were effected by peatland water table level, while the others properties were not impacted.Keywords : chemical properties, peatland, peatland managemen, physical properties